An in vivo model of focal light emitting diode-induced cone photoreceptor phototoxicity in adult pigmented mice: Protection with bFGF. (October 2021) - Miralles de Imperial-Ollero, Juan A.; Gallego-Ortega, Alejandro; Norte-Muñoz, María; Di Pierdomenico, Johnny; Valiente-Soriano, Francisco J.; Vidal-Sanz, Manuel
Abstract: Purpose: To develop a model of focal injury by blue light-emitting diode (LED)-induced phototoxicity (LIP) in pigmented mouse retinas and to study the effects on cone, Iba-1 + cells and retinal pigment epithelium (RPE) cell populations after administration of basic fibroblast growth factor (bFGF) and minocycline, alone or combined. Methods: In anesthetized dark-adapted adult female pigmented C57BL/6 mice, left pupils were dilated and the eye exposed to LIP (500 lux, 45 s). The retina was monitored longitudinally in vivo with SD-OCT for 7 days (d). Ex vivo, the effects of LIP and its protection with bFGF (0.5 μg) administered alone or combined with minocycline (45 mg/kg) were studied in immunolabeled arrestin-cone outer segments (a + OS) and quantified within a predetermined fixed-size circular area (PCA) centered on the lesion in flattened retinas at 1, 3, 5 or 7d. Moreover, Iba-1 + cells and RPE cell morphology were analysed with Iba-1 and ZO-1 antibodies, respectively. Results: LIP caused a focal lesion within the superior-temporal retina with retinal thinning, particularly the outer retinal layers (116.5 ± 2.9 μm to 36.8 ± 6.3 μm at 7d), and with progressive diminution of a + OS within the PCA reaching minimum values at 7d (6218 ± 342 to 3966 ± 311). Administration of bFGF alone (4519 ± 320) or in combination with minocycline (4882 ± 446) had a significant effect on a + OS survival at 7d and Iba-1 + cell activation was attenuated in the groups treated with minocycline. In parallel, the RPE cell integrity was progressively altered after LIP and administration of neuroprotective components had no restorative effect at 7d. Conclusions: LIP resulted in progressive outer retinal damage affecting the OS cone population and RPE. Administration of bFGF increased a + OS survival but did not prevent RPE deterioration. Highlights: Bullet points: Focal lesion after LED phototoxicity in the pigmented mouse retina. Single bFGF administration protects cones after focal LED-induced phototoxicity. Minocycline reduces microglial activation but not phototoxicity-induced cone loss. Neither bFGF nor minocycline prevents phototoxicity-induced RPE degeneration.